Contesting world order? : socioeconomic rights and global justice movements - Wills, Joe (Cambridge : Cambridge University Press, 2017)
What do equality, dignity and rights mean in a world where eight men own as much wealth as half the world's population? Contesting World Order? Socioeconomic Rights and Global Justice Movements examines how global justice movements have engaged the language of socioeconomic rights to contest global institutional structures and rules responsible for contributing to the persistence of severe poverty. Drawing upon perspectives from critical international relations studies and the activities of global justice movements, this book evaluates the'counter-hegemonic' potential of socioeconomic rights discourse and its capacity to contribute towards an alternative to the prevailing neo-liberal'common sense' of global governance.
Machine generated contents note: 1. Power, hegemony and world order; 2. Neo-liberal globalisation and socioeconomic rights: an overview; 3. Food security vs food sovereignty: the contestation of the meaning of the right to food under international law; 4. Intellectual property, the right to health and the global access to medicines campaign; 5. A commodity or a right? Evoking the human right to water to challenge neo-liberal water governance.
Title from publisher's bibliographic system (viewed on 03 May 2017).
Keywords: Social justice; Human rights movements; Economic -- Sociological aspects